2014
DOI: 10.18093/0869-0189-2014-0-3-86-98
|View full text |Cite
|
Sign up to set email alerts
|

Twice Daily N-Acetylcysteine 600 Mg for Exacerbations of Chronic Obstructive Pulmonary Disease (Pantheon): A Randomised, Double-Blind Placebo-Controlled Trial

Abstract: SummaryBackground. Increased oxidative stress and inflammation has a role in the pathogenesis of chronic obstructive pulmonary disease (COPD). Drugs with antioxidant and anti-inflammatory properties, such as N-acetylcysteine, might provide a useful therapeutic approach for COPD. We aimed to assess whether N-acetylcysteine could reduce the rate of exacerbations in patients with COPD. Methods. In our prospective, randomised, double-blind, placebo-controlled, parallel-group study, we enrolled patients aged 40-80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 25 publications
3
47
0
7
Order By: Relevance
“…The oral phosphodiesterase‐4 inhibitor, roflumilast, is associated with fewer exacerbations in COPD patients with a phenotype of chronic bronchitis and history of prior exacerbations . Oral mucolytic agents such as N ‐acetylcysteine also reduce acute exacerbations . Vaccination against both influenza and pneumococcal infections is advocated as part of overall care of COPD patients.…”
Section: Reducing Future Risk Of Exacerbationsmentioning
confidence: 99%
“…The oral phosphodiesterase‐4 inhibitor, roflumilast, is associated with fewer exacerbations in COPD patients with a phenotype of chronic bronchitis and history of prior exacerbations . Oral mucolytic agents such as N ‐acetylcysteine also reduce acute exacerbations . Vaccination against both influenza and pneumococcal infections is advocated as part of overall care of COPD patients.…”
Section: Reducing Future Risk Of Exacerbationsmentioning
confidence: 99%
“…To further dissect the effect of azithromycin on CD4 and CD8 T cells, we therefore investigated granzyme B production in T cells exposed to azithromycin (at concentrations that are physiologically relevant) in an in vitro model of T‐cell activation. Given the suggested role of high‐dose n‐acetyl cysteine in reducing COPD exacerbations, we assessed this treatment in parallel with azithromycin. Granzyme B was produced by less than 5% of non‐stimulated T cells.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the effects of azithromycin and n‐acetyl cysteine on granzyme B production, an in vitro assay was utilized . N‐acetyl cysteine was investigated based on its reported effectiveness in preventing exacerbations in COPD . Mononuclear cells were isolated from peripheral blood from the five healthy human donors using Lymphoprep (Axis‐Shield, Oslo, Norway), according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…19 Contrary to these findings, a study from china gives a new hope as N-acetylcysteine in double dose reduced the number of exacerbations when given along with backup inhaled treatment, but head-to-head comparison is still needed. 20 There were some concerns regarding the drug delivery in COPD especially with tiotropium given by Respimat device. Studies showed more number of deaths in the treatment arm as compared to placebo.…”
Section: Review Of Literature Newer Innovations In Pharmacotherapy-mentioning
confidence: 99%